Therapies for triple negative breast cancer. (May 2015) - Andreopoulou, Eleni; Schweber, Sarah J; Sparano, Joseph A; McDaid, Hayley M
<x xml:space="preserve">Abstract</x> Introduction: Triple negative breast cancer (TNBC) is a heterogeneous disease associated with a high risk of recurrence, and therapeutic options are currently limited to cytotoxic therapy. Germ-line mutations may occur in up to 20% of unselected patients with TNBC, which may serve as a biomarker identifying which patients may have tumors that are particularly sensitive to platinums and/or inhibitors of poly(ADP-ribose)polymerase. A substantial proportion of patients with TNBCs not associated with germ-line BRCA mutations may have tumors that are 'BRCA-like', rendering those individuals potential candidates for similar strategies. Areas covered: The purpose of this review is to highlight the current standard and experimental treatment strategies. Expert opinion: Recent research that has illuminated the molecular heterogeneity of the disease rationalizes its diverse biological behavior and differential response to chemotherapy. Modern technology platforms provide molecular signatures that can be mined for therapeatic interventions. Target pathways that are commonly dysregulated in cancer cells control cellular processes such as apoptosis, proliferation, angiogenesis, DNA repair, cell cycle progression, immune modulation and invasion, and metastasis. Novel trial design and re-defined endpoints as surrogates to clinical outcome have been introduced to expedite the development of breakthrough therapies to treat high-risk early-stage breast cancer.